A DESCRIPTIVE STUDY ON ENGLISH TEACHING METHOD USED BY THE TEACHER AT THE FOURTH YEAR OF SD N 1 PABELAN KARTASURA - Wijayanto, Gandi (2010)
In this research paper the writer describes the information about the procedure of teaching English vocabulary, kinds of technique used in teaching vocabulary, then the strength and weakness of the technique used by the teacher. This research uses descriptive qualitative study that uses the English teacher and observation, interview, and document. The subject of this research is limited to the student of fourth class students of SD N I Pabelan Kartasura. The results of the study show that: a) the goal of the teaching English in SD N I Pabelan Kartasura, is to develop the student's motivation on understanding the English language, b) the method of teaching English applied by the teacher is Total Physical Response (TPR), c) the strength and weaknesses of the Technique. The strengths are: the students feels comfort and more fun when they receive the materials, the students are interested in and attracted to the media, the method increases their self-confidence. Then the weaknesses are: any student is usually shy if they have the command from the teacher to answer the question in front of the class, half of the students especially, who sit at the back, usually make noise, and then the teacher must handle the students more seriously.